Reproductive health education and early sexual behavior prevention assistance for Madrasah Aliyah students in Bandung - Ermina Widiyastuti; Meta Maulida Damayanti; Ismet Muchtar Nur; Tita Barriah Siddiq; Indri Budiarti; Ayu Prasetia (University of Merdeka Malang, 2024)
Health reproduction knowledge is a crucial factor in preventing acts of early sexual behavior. Early sexual behavior is reflected in many ways, from attraction to different sexes to building a relationship and making physical contact. Adequate knowledge of sexuality in teenagers especially in health reproduction would prevent teenagers from acting in early sexual behavior. This activity aims to increase knowledge about the health of reproductive organs and the prevention of early sexual intercourse among Madrasah Aliyah students. The method used is education regarding the health of reproductive organs, pre-marital sexual psychology, and social jurisprudence approaches. All material is presented interestingly and interactively. This activity found that 63 percent of the participants had previous knowledge of this topic. More than 50 percent of respondents were students, and students had quite good knowledge about reproductive health. Madrasah Aliyah students already have sufficient knowledge about reproductive health, but it has not yet been seen whether it is enough to prevent students from premature sexual behavior. However, we do not have any data regarding the act of early sexual behavior among respondents or how knowledge in health reproduction would relate to the act of early sexual behavior.